Lignin-based porous carbon material for supercapacitor electrode and preparation method and application thereof

By reacting corn stalk fermentation residue with inorganic alkaline solution and activating with potassium hydroxide, a lignin-based porous carbon material with rich pore structure was solved, and the existing electrode materials had lower capacitance and poor cycle stability were achieved. Highly efficient energy storage and good electrochemical properties.

CN119170425APending Publication Date: 2024-12-20HUAXIAN DACHAOLIN BUSSAN
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411300308.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The specific capacitance of lignin-based carbon in the existing supercapacitor electrode materials is lower and the cycle stability is poor, which fails to achieve the ideal energy storage effect.

Method used

The residue of alcohol prepared by fermenting corn stalks is mixed with an inorganic alkaline solution. After heating and pressurization, the acid solution is added to neutralize it after filtration, lignin is precipitated, and mixed with potassium hydroxide for two steps to be activated, resulting in rich and rich production. Porous structure of lignin-based porous carbon material.

Benefits of technology

The prepared lignin-based porous carbon material has high specific surface area and excellent electrochemical properties, low resistance, good conductivity, good cycling stability under high current density, and a capacitance retention rate of up to 88%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a lignin-based porous carbon material for a supercapacitor electrode and a preparation method and application of the lignin-based porous carbon material, and relates to the technical field of supercapacitor electrode material preparation. The lignin-based porous carbon material is obtained by treating residues generated in preparation of alcohol through corn straw fermentation to obtain lignin, mixing the lignin with potassium hydroxide, and performing two-step activation. According to the preparation method, residues obtained after straw fermentation are adopted as raw materials, reutilization of the residues has high practicability and good economic value, the preparation method is simple, reaction conditions are not harsh, industrial implementation is easy, and batch production and application can be achieved. The lignin-based porous carbon material prepared by the method provided by the embodiment of the invention has microporous and mesoporous structures at the same time. When the composite material is applied to a supercapacitor electrode material, the composite material is low in resistance, good in conductivity, excellent in electrochemical performance and good in cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of supercapacitor electrode material preparation, and in particular, to a lignin-based porous carbon material for supercapacitor electrodes and a preparation method and application thereof. Background Art

[0002] Supercapacitors are a new type of energy storage device. There are many types of supercapacitor electrode materials, such as carbon materials, conductive polymers, metal oxides and composite materials. The electrode material plays a vital role in the capacitance performance of supercapacitors. Most of these carbon materials are prepared from coal or fossil petroleum materials, which are non-renewable and unsustainable. Therefore, lignin as a carbon material precursor has attracted research attention due to its reproducibility, low cost and biodegradability. Surprisingly, lignin has a high carbon content and good thermal stability. Therefore, the preparation of supercapacitors using lignin has been widely studied.

[0003] Lignin is a biomass waste that is the main component of waste liquid in the pulp and paper industry and industrial residue in the fuel ethanol industry, and only less than 2% is effectively utilized. How to achieve high added value comprehensive utilization of lignin to improve the economic benefits of pulp and paper and fuel ethanol production is becoming a hot issue of concern to scientific researchers. Because lignin has a large number of benzene ring structures in its molecular chain and a carbon content of more than 50%, it has a high yield and is considered to be an ideal precursor for carbon materials.

[0004] At present, a large number of researchers have conducted in-depth research on lignin-based carbon supercapacitors, but their specific capacitance is low and their cycle stability is poor, and the energy storage effect is far from ideal. Summary of the invention

[0005] The purpose of the present application is to provide a method for preparing a lignin-based porous carbon material for supercapacitor electrodes. The preparation method is simple, the reaction conditions are not harsh, it is easy to implement in industry, and can be mass-produced and applied.

[0006] Another object of the present application is to provide a lignin-based porous carbon material prepared by the above method, which has a rich pore structure and excellent energy storage effect.

[0007] Another object of the present application is to provide an application of the lignin-based porous carbon material prepared by the above method in a supercapacitor electrode material, which has excellent electrochemical properties.

[0008] The present application solves the technical problem by adopting the following technical solution.

[0009] First, the present invention provides a method for preparing a lignin-based porous carbon material for a supercapacitor electrode, which comprises the following steps:

[0010] Step A: mixing the residue of corn stalk fermentation to prepare alcohol with an inorganic alkaline solution, heating and pressurizing to fully react and dissolve, filtering and retaining the filtrate, adding acid solution to the filtrate for neutralization, then adding water to precipitate lignin, and then centrifugally separating, washing with water, and drying to obtain lignin for later use;

[0011] Step B: After mixing lignin and potassium hydroxide, pre-activate them in a muffle furnace, cool them, and then transfer them to a tubular furnace for high-temperature activation in a nitrogen atmosphere and cool them to obtain a lignin-based porous carbon material.

[0012] Second, the present invention provides a lignin-based porous carbon material prepared by the above method. The lignin-based porous carbon material is a black powder with a specific surface area of ​​2538.9-2478.8 m 2 / g, with a total pore volume of 1.3-1.22cm 3 / g, the pore types include micropores and mesopores, among which the specific surface area of ​​micropores is 2318.8-2211.82m 2 / g, micropore volume is 0.97-0.939cm 3 / g, mesopore specific surface area is 193.2-187.6m 2 / g, and the mesopore volume is 0.27-0.246cm 3 / g, bulk density is 0.91-0.86m 3 / g, and the particle size distribution is 100-1000nm.

[0013] Third, an embodiment of the present application provides an application of the lignin-based porous carbon material prepared by the above method in a supercapacitor electrode material.

[0014] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:

[0015] The embodiment of the present application provides a method for preparing a lignin-based porous carbon material for supercapacitor electrodes. The raw material used is the residue after straw fermentation. The reuse of the residue is very practical and has good economic value. The separation and extraction of lignin from the residue of microbial enzymatic hydrolysis of corn straw can solve the loss problem of the process of preparing energy alcohol by microbial enzymatic hydrolysis of corn straw, which will be conducive to the promotion of this new green and environmentally friendly process and sustainable development. The subsequent step is to generate micropores at low temperature and a part of mesopores at high temperature by a two-step activation method. The method is simple, the reaction conditions are not harsh, it is easy to implement in industry, and can be used in mass production.

[0016] The embodiment of the present application provides a lignin-based porous carbon material prepared by the above method, which has both microporous and mesoporous structures, indicating that the void structure is well developed, which can expose more active sites and is beneficial to the infiltration of the electrolyte. At the same time, the mesopores can be used for the transmission and diffusion of ions, thereby accelerating the transmission efficiency of the ions, and the micropores can be used to enhance the storage of charges. The porous structure is beneficial to the energy storage of the double-layer capacitor.

[0017] The embodiment of the present application provides an application of the lignin-based porous carbon material prepared by the above method in a supercapacitor electrode material, which has low resistance, good conductivity, and excellent electrochemical properties. The specific capacitance is as high as 795F / g at a current density of 2A / g. At the same time, it has good cycle stability. After 10,000 cycles at a high current density, the capacitance retention rate is still as high as 88%. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0019] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0020] The present invention provides a method for preparing a lignin-based porous carbon material for a supercapacitor electrode, which comprises the following steps:

[0021] Step A: mixing the residue of corn stalk fermentation to prepare alcohol with an inorganic alkaline solution, heating and pressurizing to fully react and dissolve, filtering and retaining the filtrate, adding acid solution to the filtrate for neutralization, then adding water to precipitate lignin, and then centrifugally separating, washing with water, and drying to obtain lignin for later use;

[0022] Step B: After mixing lignin and potassium hydroxide, pre-activate them in a muffle furnace, cool them, and then transfer them to a tubular furnace for high-temperature activation in a nitrogen atmosphere and cool them to obtain a lignin-based porous carbon material.

[0023] The present application separates and extracts lignin from the residue of corn stalks hydrolyzed by microorganisms. During the microbial fermentation of energy alcohol and the separation from the residue, the lignin is in a relatively mild state, so the lignin retains the active groups of lignin well and has good economic value. Separating and extracting lignin from the residue of corn stalks hydrolyzed by microorganisms can solve the loss problem of the process of preparing energy alcohol by corn stalks hydrolyzed by microorganisms, which will be conducive to the promotion of this new green and environmentally friendly process and sustainable development.

[0024] At low temperatures, due to the intercalation and strong etching effects of KOH, it can not only react with the surface of lignin, but also enter the irregular graphite interlayers to react with the inner carbon. As the activation temperature continues to increase, KOH reacts with some carbon atoms with lower activation energy in the raw material to produce a large number of micropores. The K2C generated at high temperatures will be reduced to metallic potassium. When the activation temperature exceeds 762°C, metallic potassium produces potassium vapor, which is inserted and diffused into the carbon layer, stretching the layers to deform or twist them, and generating new pores. The activator continues to react and enters the pores, transforming some micropores into mesopores. The mesopore content gradually increases. While the pores are expanding, the intercalation reaction continues, changing the pore depth while changing the pore diameter.

[0025] The reaction mechanism is as follows:

[0026] 2KOH→K2O+H2O (1)

[0027] C+H2O→H2+CO (2)

[0028] K2O+H2→2K+H2O (3)

[0029] K2O+C→2K+CO (4)

[0030] CO+H2O→H2+CO2 (5)

[0031] K2O+CO2→K2CO3 (6)

[0032] In some embodiments of the present application, the inorganic alkaline solution in the above step A is one or more of sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide solution, and ammonia water.

[0033] In some embodiments of the present application, the mass ratio of the raw materials in the above step A is: 100 parts of the residue of corn stalk fermentation to prepare alcohol, and 300-600 parts of an inorganic alkaline solution with a concentration of 15-30%. Lignin is dissolved in the inorganic alkaline solution and separated from other components by filtration. After the lignin solution is neutralized with acid, the lignin is precipitated, and then centrifuged, washed with water, and dried to obtain enzymatic lignin. Therefore, the solubility of lignin in the alkaline solution is in the optimal range, and will not cause excessive waste of the alkaline solution.

[0034] In some embodiments of the present application, the heating temperature in the above step A is 60°C-80°C, the pressurized pressure is 0.5MPa-1.0MPa, and the reaction time is 2h-4h. This step does not require a too high reaction temperature under pressurized conditions, which saves both time and heat source. In a relatively mild state, lignin better retains the active groups of lignin, which is more conducive to the generation of pore structures in subsequent steps.

[0035] In some embodiments of the present application, lignin and potassium hydroxide are mixed in a mass ratio of 1:2-5 in the above step B. If the amount of potassium hydroxide is too little, the intercalation will be insufficient, affecting the formation of the pore structure, but if the amount of potassium hydroxide is too much, it will not only cause waste, but also increase the cost of impurity removal.

[0036] In some embodiments of the present application, in the pre-activation in the muffle furnace in the above step B, the temperature is increased to 300°C-500°C at a rate of 5°C / min-10°C / min and maintained for 2h-4h. The heating rate during the pre-activation process should not be too fast, otherwise it may cause the collapse of the pore structure.

[0037] In some embodiments of the present application, the high temperature activation in the tubular furnace in the above step B is heated at a rate of 2°C / min-5°C / min to 800°C-1000°C, and maintained for 2h-4h. The high temperature activation in the tubular furnace is heated at a slower rate, which is beneficial for gasifying and removing some impurities on the one hand, and is beneficial for the formation of mesopores on the other hand. At the same time, the temperature range is selected because when the activation temperature exceeds 762°C, metallic potassium produces potassium vapor, which is inserted and diffused into the carbon layer, stretching the layer to deform or twist it, generating new pores, and continuing the reaction activator to enter the pores, so that a part of the micropores are transformed into mesopores, and the mesopore content gradually increases. While expanding the pores, the intercalation reaction continues, and while changing the pore size, the depth of the pores is also changed, thereby forming a relatively strong pore structure.

[0038] In some embodiments of the present application, step C is also included, wherein the lignin-based porous carbon material obtained in step B is dissolved in water, heated, repeatedly washed with water, centrifuged, and dried. The main purpose of this step is to remove impurities. The activated material is naturally cooled after being discharged from the activation furnace, and then pure water is added for dissolution. The purpose of dissolution is mainly to separate the K2CO3, a small amount of KOH, etc. mixed in the material from the activated carbon. Indirect heating (for example: water bath heating or oil bath heating) is used during the dissolution process, and the temperature is controlled at 60-80°C to avoid water evaporation, thereby further improving the solubility of salts, making the material separation more thorough, and facilitating centrifugation and subsequent drying.

[0039] The present application provides a lignin-based porous carbon material prepared by the above method. The lignin-based porous carbon material is in the form of black powder with a specific surface area of ​​2538.9-2478.8 m 2 / g, with a total pore volume of 1.3-1.22cm 3 / g, the pore types include micropores and mesopores, among which the specific surface area of ​​micropores is 2318.8-2211.82m 2 / g, micropore volume is 0.97-0.939cm 3 / g, mesopore specific surface area is 193.2-187.6m 2 / g, and the mesopore volume is 0.27-0.246cm 3 / g, bulk density is 0.91-0.86m 3 / g, particle size distribution is 100-1000nm

[0040] The embodiment of the present application provides an application of the lignin-based porous carbon material prepared by the above method in the preparation of supercapacitor electrode materials.

[0041] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0042] Example 1

[0043] The present application embodiment provides a lignin-based porous carbon material for supercapacitor electrodes, and the specific preparation method includes the following steps:

[0044] Step A: 100 parts of the residue obtained by fermenting corn stalks to prepare alcohol are mixed with 300 parts of a 15% by mass sodium hydroxide solution in a certain proportion, and reacted for 2 hours in a reactor at a temperature of 65°C ± 5°C and a pressure of 0.5 MPa to fully react and dissolve, and the filtrate is retained after filtration, and an acid solution is first added to the filtrate for neutralization, and then water is added to precipitate lignin, and then lignin is obtained by centrifugation, washing with water, and drying for standby use;

[0045] Step B: After lignin and potassium hydroxide are mixed in a mass ratio of 1:2, they are pre-activated in a muffle furnace, cooled, and then transferred to a tubular furnace for high-temperature activation in a nitrogen atmosphere, and cooled to obtain a lignin-based porous carbon material.

[0046] The pre-activation conditions in the muffle furnace are: heating rate of 5°C / min to 300°C and maintaining for 4h.

[0047] The conditions for high temperature activation in the tube furnace are: heating up to 800°C at a rate of 2°C / min and maintaining for 4h.

[0048] Example 2

[0049] The present application embodiment provides a lignin-based porous carbon material for supercapacitor electrodes, and the specific preparation method includes the following steps:

[0050] Step A: 100 parts of the residue obtained by fermenting corn stalks to prepare alcohol are mixed with 600 parts of a 20% potassium hydroxide solution by mass in a certain proportion, and reacted for 4 hours in a reactor at a temperature of 70°C ± 5°C and a pressure of 0.8 MPa to fully react and dissolve, and the filtrate is retained after filtration, and an acid solution is first added to the filtrate for neutralization, and then water is added to precipitate lignin, and then lignin is obtained by centrifugation, washing with water, and drying for standby use;

[0051] Step B: After lignin and potassium hydroxide are mixed in a mass ratio of 1:5, they are pre-activated in a muffle furnace, cooled, and then transferred to a tubular furnace for high-temperature activation in a nitrogen atmosphere, and cooled to obtain a lignin-based porous carbon material.

[0052] The pre-activation conditions in the muffle furnace are as follows: heating rate is 10°C / min to 500°C and maintained for 2h.

[0053] The conditions for high temperature activation in the tube furnace are: heating up to 900°C at a rate of 5°C / min and maintaining for 2h.

[0054] Example 3

[0055] The present application embodiment provides a lignin-based porous carbon material for supercapacitor electrodes, and the specific preparation method includes the following steps:

[0056] Step A: 100 parts of the residue obtained by fermenting corn stalks to prepare alcohol are mixed with 400 parts of 30% calcium hydroxide solution by mass in a certain proportion, and reacted for 3 hours in a reactor at a temperature of 75°C ± 5°C and a pressure of 1.0 MPa to fully react and dissolve, and the filtrate is retained after filtration, and an acid solution is first added to the filtrate for neutralization, and then water is added to precipitate lignin, and then lignin is obtained by centrifugation, washing with water, and drying for standby use;

[0057] Step B: After lignin and potassium hydroxide are mixed in a mass ratio of 1:3, they are pre-activated in a muffle furnace, cooled, and then transferred to a tubular furnace for high-temperature activation in a nitrogen atmosphere, and cooled to obtain a lignin-based porous carbon material.

[0058] The pre-activation conditions in the muffle furnace are: heating rate of 6°C / min to 400°C and maintaining for 3h.

[0059] The conditions for high temperature activation in the tube furnace are: heating rate of 4°C / min to 1000°C and maintaining for 4h.

[0060] Example 4

[0061] The present application embodiment provides a lignin-based porous carbon material for supercapacitor electrodes, and the specific preparation method includes the following steps:

[0062] Step A: 100 parts of the residue obtained by fermenting corn stalks to prepare alcohol are mixed with 500 parts of 15% ammonia water in proportion, and reacted for 3.5 hours in a reactor at a temperature of 70°C ± 5°C and a pressure of 0.7 MPa to fully react and dissolve, and the filtrate is retained after filtration, and an acid solution is first added to the filtrate for neutralization, and then water is added to precipitate lignin, and then centrifugation, water washing, and drying are performed to obtain lignin for standby use;

[0063] Step B: After lignin and potassium hydroxide are mixed in a mass ratio of 1:4, they are pre-activated in a muffle furnace, cooled, and then transferred to a tubular furnace for high-temperature activation in a nitrogen atmosphere, and cooled to obtain a lignin-based porous carbon material.

[0064] Step C: dissolving the lignin-based porous carbon material obtained in step B in water, heating, repeatedly washing with water, centrifuging, and drying.

[0065] The pre-activation conditions in the muffle furnace are: heating rate of 8°C / min to 500°C and maintaining for 4h.

[0066] The conditions for high temperature activation in the tube furnace are: heating rate of 4°C / min to 1000°C and maintaining for 4h.

[0067] Comparative Example 1

[0068] This comparative example provides a lignin-based porous carbon material for supercapacitor electrodes, and the specific preparation method comprises the following steps:

[0069] Step A: 100 parts of the residue obtained by fermenting corn stalks to prepare alcohol are mixed with 300 parts of a 15% by mass sodium hydroxide solution in a certain proportion, and reacted for 2 hours in a reactor at a temperature of 65°C ± 5°C and a pressure of 0.5 MPa to fully react and dissolve, and the filtrate is retained after filtration, and an acid solution is first added to the filtrate for neutralization, and then water is added to precipitate lignin, and then lignin is obtained by centrifugation, washing with water, and drying for standby use;

[0070] Step B: After mixing lignin and potassium hydroxide in a mass ratio of 1:2, directly activate them at high temperature in a tubular furnace under a nitrogen atmosphere, and cool them to obtain a lignin-based porous carbon material.

[0071] Specifically, the conditions for high temperature activation in the tube furnace are: heating up to 800° C. at a heating rate of 2° C. / min and maintaining for 4 h.

[0072] Comparative Example 2

[0073] This comparative example provides a lignin-based porous carbon material for supercapacitor electrodes, and the specific preparation method comprises the following steps:

[0074] The lignin used was commercially available lignin (CAS: 8068-03-9, purity: 99%, manufacturer: Pandex Shanghai International Trade Co., Ltd.). After the lignin and potassium hydroxide were mixed in a mass ratio of 1:2, they were first pre-activated in a muffle furnace, cooled, and then transferred to a tubular furnace for high-temperature activation in a nitrogen atmosphere, and cooled to obtain a lignin-based porous carbon material.

[0075] The pre-activation conditions in the muffle furnace are: heating rate of 5°C / min to 300°C and maintaining for 4h.

[0076] The conditions for high temperature activation in the tube furnace are: heating up to 800°C at a rate of 2°C / min and maintaining for 4h.

[0077] Experimental Example 1

[0078] The specific surface area and pore structure (BET) analysis of the lignin-based porous carbon materials prepared in Examples 1-4 and Comparative Examples 1-2 were performed, and the samples were subjected to dry nitrogen isothermal adsorption analysis at 77K (liquid nitrogen bath) using a micropore analyzer (ASAP 2020). The surface area, sample diameter of the pores, and pore volume of the samples were calculated using the Brunauer-Emmett-Teller (BET) Barrett-Joyner-Halenda (BJH) analysis theory. The specific test results are shown in Table 1:

[0079] Table 1. Specific surface area and pore structure test results

[0080]

[0081]

[0082] It can be seen from Table 1 that the specific surface areas of the lignin-based porous carbon materials of Examples 1-4 of the present application are as high as 2538.9-2478.8 m 2 / g, the total pore volume reaches 1.3-1.22cm 3 / g, of which the micropore specific surface area is 2318.8-2211.82m 2 / g, micropore volume is 0.97-0.939cm 3 / g, mesopore specific surface area is 193.2-187.6m 2 / g, and the mesopore volume is 0.27-0.246cm 3 / g. While Comparative Example 1 directly uses a tubular furnace for activation, and the absence of pre-activation in the air will result in insufficient formation of the pore structure, thereby reducing both the specific surface area and the pore volume. It can be seen that by means of a two-step activation method, micropores are first generated at low temperatures, and a portion of mesopores are generated in a high temperature chamber. Mesopores can be used for the transmission and diffusion of ions, thereby accelerating the transmission efficiency of ions, and micropores can be used to enhance the storage of charges, so the porous structure is beneficial to the energy storage of double-layer capacitors. As can be seen from Comparative Example 2, the porous carbon material obtained by using commercially available lignin as a raw material has a specific surface area and pore volume that are significantly lower than the samples of Examples 1-4, indicating that the lignin obtained by the present application method can be used as a raw material to obtain a carbon material with a more developed pore structure. This is because the lignin is in a relatively mild state during the separation of the residue, so that the lignin retains the active groups of the lignin better, which is more conducive to the generation of the pore structure in the subsequent steps. At the same time, it has good economic value. Separating and extracting lignin from the residue of microbial enzymatic hydrolysis of corn straw can solve the loss problem of the process of preparing energy alcohol by microbial enzymatic hydrolysis of corn straw, which will be conducive to the promotion of this new green and environmentally friendly process and sustainable development.

[0083] Experimental Example 2

[0084] Electrochemical performance test:

[0085] The electrochemical properties of the lignin-based porous carbon materials prepared in Examples 1-4 and Comparative Examples 1-2 were characterized by a three-electrode system. The electrolyte was a 1mol / L H2SO4 electrolyte. The saturated calomel electrode (SCE) was used as the reference electrode, the platinum sheet was used as the counter electrode, and the sample was used as the working electrode. The voltage window of the test was set to 0-0.8V (vs. SCE). When the material was assembled into a symmetrical supercapacitor device, the voltage window was 0-1.0V when 1mol / L H2SO4 was used as the electrolyte; when the ionic liquid (EMIMBF4) was used as the electrolyte, the voltage window was 0-3.5V. The diaphragm used for the symmetrical supercapacitor was a polypropylene film, which was placed between two disc carbon electrodes of the same mass (active substance) and size to assemble into a simple device with a sandwich structure.

[0086] (1) Galvanostatic Charge-Discharge (GCD) test was performed on the LAND CT3002A blue battery test system with current densities of 2, 4, 6, 8, and 10 A / g. The mass specific capacitance C S The size of (F / g) can be estimated based on the GCD curve, and the calculation formula is as follows:

[0087]

[0088] Among them, I represents the current size, the unit is A; Δt represents the charging or discharging time, the unit is s; ΔV represents the range of change of the voltage window, the unit is V; m represents the mass of the electrode active material, the unit is g.

[0089] (2) Electrochemical impedance spectroscopy (EIS) test: This paper uses a Chenhua CHI 760E electrochemical workstation to test and obtain the electrochemical impedance spectrum of the supercapacitor under open circuit voltage. The voltage amplitude used is 5 mV and the frequency is 0.01 Hz to 100000 Hz.

[0090] (3) Cyclic stability test of materials in supercapacitors. This paper uses the LAND CT200 2A battery testing system to test the cyclic stability of materials by cycling 10,000 times at a constant current density of 10 A / g.

[0091] Table 2. Electrochemical test results

[0092]

[0093]

[0094] As can be seen from Table 2, the lignin-based porous carbon material prepared in this application has excellent electrochemical properties, with a specific capacitance of up to 795F / g at a lower hydrogen current density (2A / g), and a specific capacitance of up to 627F / g at a higher current density (10A / g). At the same time, it can be seen that the capacitance gradually decreases with the increase of current density. This is because when the current density continues to increase, the charge and discharge time decreases, and the rate of the electrochemical reaction of the active substance lags behind the electron transfer rate during charge and discharge. Before reaching a certain capacity value, the voltage has reached the set value to stop charging and discharging, so the capacitance value will be reduced to a certain extent. The resistance of the lignin-based porous carbon material prepared in this application is less than 1, indicating that the conductivity is good. At the same time, after 10,000 cycles at high current density, the capacitance retention rate is as high as 88%.

[0095] The electrochemical performance of the samples of Comparative Examples 1 and 2 is also far inferior to that of the samples of Examples 1-4. This is because the specific surface area and pore volume of the samples prepared by the preparation method of Comparative Examples 1-2 are smaller than those of Examples 1-4, which directly leads to a slower electron transmission rate, poor conductivity, and poor electrochemical performance. The capacitance retention rate of Comparative Example 1 is only 52%. We speculate that this is because the one-step activation is used in the preparation process, the stability of its pore structure is poor, and the collapse of the pore structure during the cycle process leads to a significant decline in specific capacitance.

[0096] Experimental Example 3

[0097] Bulk density analysis

[0098] Take a sample, mix the conductive agent carbon black and the binder (PTFE) in a mass ratio of 8:1:1, add an appropriate amount of ethanol as a dispersant, mix and grind in an agate mortar, then drop into an infrared mold and dry in a vacuum drying oven at 50 degrees. Use an infrared tablet press (769YP-30T) to apply a force of 10MPa to tablet it, and use a micrometer to measure the length, width, and height of the pressed carbon. The volume is length * width * height. And accurately weigh it, and the resulting bulk density is the mass divided by the volume. The test results of the bulk density of the lignin-based porous carbon materials prepared in Examples 1-4 and Comparative Examples 1-2 are shown in Table 3:

[0099] Table 3. Bulk density test results

[0100] <![CDATA[Bulk density (m 3 / g)]]> Example 1 0.89 Example 2 0.86 Example 3 0.87 Example 4 0.91 Comparative Example 1 0.57 Comparative Example 2 0.52

[0101] It can be seen from Table 3 that the bulk density of the carbon materials prepared in Examples 1-4 is between 0.91 and 0.86 m 3 / g, which is significantly higher than the data of the samples in Comparative Examples 1-2, and also indicates that the carbon materials prepared in Examples 1-4 have a well-developed pore structure, which leads to a decrease in the voids and an increase in the packing density.

[0102] In summary, the embodiment of the present application provides a method for preparing a lignin-based porous carbon material for a supercapacitor electrode. The raw material used is the residue after straw fermentation. The reuse of the residue is very practical and has good economic value. Separating and extracting lignin from the residue of microbial enzymatic hydrolysis of corn straw can solve the loss problem of the process of preparing energy alcohol by microbial enzymatic hydrolysis of corn straw, which will be conducive to the promotion of this new green and environmentally friendly process and sustainable development. The subsequent steps are activated in two steps. Micropores are first generated at low temperature. At high temperature, metallic potassium generates potassium vapor. The potassium vapor is inserted and diffused into the carbon layer, stretching the layer to deform or twist it, generating new pores, and continuing the reaction. The activator enters the pores, so that a part of the micropores are transformed into mesopores, and the mesopore content gradually increases. While expanding the pores, the intercalation reaction continues, and the depth of the pores is changed while changing the pore size. The method is simple, the reaction conditions are not harsh, it is easy to implement in industry, and can be applied in mass production.

[0103] The present invention provides a lignin-based porous carbon material prepared by the above method, which has a microporous and mesoporous structure and a specific surface area of ​​2538.9-2478.8 m 2 / g, the total pore volume reaches 1.3-1.22cm 3 / g, of which the micropore specific surface area is 2318.8-2211.82m2 / g, micropore volume is 0.97-0.939cm 3 / g, mesopore specific surface area is 193.2-187.6m 2 / g, and the mesopore volume is 0.27-0.246cm 3 / g. The well-developed void structure can expose more active sites, which is beneficial to the infiltration of electrolyte. At the same time, the mesopores can be used for the transmission and diffusion of ions, thereby accelerating the transmission efficiency of ions. The micropores can be used to enhance the storage of charges. The porous structure is beneficial to the energy storage of double-layer capacitors.

[0104] The present application provides an application of the lignin-based porous carbon material prepared by the above method in a supercapacitor electrode material, which has low resistance, good conductivity, and excellent electrochemical properties. The specific capacitance is as high as 795F / g at a lower hydrogen current density (2A / g), and the specific capacitance can reach 627F / g at a higher current density (10A / g). At the same time, it has good cycle stability, and the capacitance retention rate is as high as 88% after 10,000 cycles at a high current density.

[0105] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0106] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a lignin-based porous carbon material for supercapacitor electrodes, characterized in that: The following steps are involved: Step A: mixing the residue of corn stalk fermentation to prepare alcohol with an inorganic alkaline solution, heating and pressurizing to fully react and dissolve, filtering and retaining the filtrate, adding acid solution to the filtrate for neutralization, then adding water to precipitate lignin, and then centrifugally separating, washing with water, and drying to obtain lignin for later use; Step B: After mixing lignin and potassium hydroxide, pre-activate them in a muffle furnace, cool them, and then transfer them to a tubular furnace for high-temperature activation in a nitrogen atmosphere and cool them to obtain a lignin-based porous carbon material.

2. The method for preparing a lignin-based porous carbon material for supercapacitor electrodes according to claim 1, characterized in that: The inorganic alkaline solution in step A is one or more of sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide solution and ammonia water.

3. The method for preparing a lignin-based porous carbon material for supercapacitor electrodes according to claim 1, characterized in that: By weight, 100 parts of the residue from fermenting corn stalks to prepare alcohol and 300-600 parts of an inorganic alkaline solution with a concentration of 15-30wt% are added.

4. The method for preparing a lignin-based porous carbon material for supercapacitor electrodes according to claim 1, characterized in that: In the step A, the heating temperature is 60° C.-80° C., the pressurizing pressure is 0.5 MPa-1.0 MPa, and the reaction time is 2 h-4 h.

5. The method for preparing a lignin-based porous carbon material for supercapacitor electrodes according to claim 1, characterized in that: In the step B, lignin and potassium hydroxide are mixed in a mass ratio of 1:2-5.

6. The method for preparing a lignin-based porous carbon material for supercapacitor electrodes according to claim 1, characterized in that: In the step B, the pre-activation conditions in the muffle furnace are: heating at a rate of 5°C / min-10°C / min to 300°C-500°C, and maintaining for 2h-4h.

7. The method for preparing a lignin-based porous carbon material for supercapacitor electrodes according to claim 1, characterized in that: In the step B, the high temperature activation conditions in the tube furnace are: heating rate is 2°C / min-5°C / min to 800°C-1000°C, and maintained for 2h-4h.

8. The method for preparing a lignin-based porous carbon material for supercapacitor electrodes according to claim 1, characterized in that: The method further comprises step C, dissolving the lignin-based porous carbon material obtained in step B in water, heating, repeatedly washing with water, centrifuging, and drying.

9. A lignin-based porous carbon material prepared by the preparation method according to any one of claims 1 to 8, wherein: The lignin-based porous carbon material is in the form of black powder with a specific surface area of ​​2538.9-2478.8 m 2 / g, with a total pore volume of 1.3-1.22cm 3 / g, the pore types include micropores and mesopores, among which the specific surface area of ​​micropores is 2318.8-2211.82m 2 / g, micropore volume is 0.97-0.939cm 3 / g, mesopore specific surface area is 193.2-187.6m 2 / g, and the mesopore volume is 0.27-0.246cm 3 / g, bulk density is 0.91-0.86m 3 / g, and the particle size distribution is 100-1000nm.

10. Use of the lignin-based porous carbon material prepared by the preparation method according to any one of claims 1 to 8 in preparing a supercapacitor electrode material.

Citation Information

Cited By

  • Preparation method of lignin applied to high-performance capacitor carbon

    CN120463958A

  • Modified lignin-based porous carbon, preparation method thereof and silicon-carbon negative electrode material

    CN122035860A